SOMATIC CELL COUNTS IN RAW MILK CONTAMINATED WITH ANTIBIOTIC RESIDUES - Ortiz Z., César (2011)
The objective of the present study was to evaluate the somatic cell count (SCC) inraw milk samples contaminated with antibiotics in Arequipa milkshed. A total of 1814 werecollected in summer 2009, and 59 of them resulted contaminated with antibiotics. SCCvalues from contaminated samples were stratified in five levels according to physiologicalstatus and milk quality requirements. The average SCC was 1520 ± 1173 x 10 3 cel/ml.Significant differences were found between levels of SCC (p<0.01).